(untitled) (TEST Ticontre. Theory Text Translation, 2018)
Since the beginning of the XXth century the notion of melancholy has gained a new perspective, generally aligning with mental illness and depressive syndromes. Nevertheless, the ancient relation between psychopathology and erotic impulse has remained unaltered, as has the Aristotelian perception of melancholy as a prerogative of the artistic genius. Given such bond between mental illness, eroticism and artistic creation, this study proposes to explore its projection in XXth-century female poetry. Indeed, in the second half of the century many female poets shared difficult and traumatic biographical experiences, as wells as an introspective approach to poetry and a focus on the representation of body and sexuality, despite psychosis and suicidal tendencies. Therefore, this essay proposes to examine the textualization of the female body and of problematic eroticism in a transnational selection of XXth-century female authors, namely Amelia Rosselli, Sylvia Plath, and Alejandra Pizarnik. A disquieting sense of depression is central in each poetics, due to their real-life experiences and traumas; nevertheless, it coexists with a vitalistic and erotic impulse that has been usually neglected by biographically-driven critical studies. On the contrary, the comparative scope of this contribution seeks to define the presence of a dichotomy between passion and anguish, thus allowing for new and more complex interpretations. A partire dal XX secolo la nozione di melancolia ha acquisito una fisionomia nuova, allineandosi generalmente con le patologie mentali e gli stati depressivi. A rimanere inalterato, tuttavia, è l’antico legame tra psicopatologia e impulso erotico, nonché la percezione aristotelica della melancolia come peculiarità del genio artistico. Appurato il vincolo tra disturbo mentale, eros e creazione artistica, risulta interessante esplorarne la proiezione nella poesia femminile contemporanea. Infatti, ad accomunare numerose poetesse attive nel secondo Novecento sono le vicende biografiche segnate da traumi psicologici e tendenze autodistruttive, oltre che il carattere introspettivo della produzione poetica e l’accento sulla rappresentazione della corporeità e delle passioni erotiche, malgrado l’incombenza della psicosi. Ci si propone quindi di approfondire lo studio delle testualizzazioni del corpo e dell’erotismo femminile problematico in una selezione di autrici coeve e dal vissuto tragico, tra cui l’italiana Rosselli, la statunitense Plath e l’argentina Pizarnik. Sebbene per tutte il paradigma fondamentale sia un senso di inquietudine derivante dalle reali patologie depressive, nella creazione artistica esso coesiste con un impulso erotico-vitalistico spesso trascurato da una critica eccessivamente legata al biografismo. Al contrario, questo contributo riscontra la presenza di un intreccio dicotomico tra passione e angoscia e quindi capace di prestare tali poetiche a una prospettiva interpretativa nuova e complessa.